No evidence for a pathogen associated with pulmonary MALT lymphoma: a metagenomics investigation - Raphaël Borie (Infectious Agents and Cancer, 2021)
Abstract Mucosa-associated lymphoid tissue (MALT) lymphoma is generally associated with chronic antigen stimulation: auto-antigens or of microbial origin. Only one study suggested association between Achromobacter xylosoxidans and pulmonary MALT lymphoma. We aimed to investigate the presence of virus or any infectious agents in pulmonary MALT lymphoma by using metagenomic next-generation sequencing (mNGS). All lung samples were centrally reviewed. The t(11;18) (q21;q21) was evaluated by FISH analysis. The snap frozen large lung biopsies were analyzed by mNGS. After lung biopsies homogenization total nucleic acids (RNA and DNA) were extracted, amplified and classified according to their taxonomic assignment, after exclusion of host DNA. We included 13 samples from pulmonary MALT lymphoma (mean age: 60.3 years, 7 women, 3 with auto-immune background) and 10 controls. The diagnosis of MALT lymphoma was confirmed for the 13 samples, 3 showed API2-MALT1 translocation (23%). No evidence of the presence of a specific pathogen was clearly identified in the group of patients with pulmonary MALT lymphoma. We identifiedA. xylosoxidans sequence in 4/13 patients and in 4/10 controls. This study did not find evidence for a DNA or RNA virus, a fungi, a parasite or a bacteria associated with pulmonary MALT lymphoma either in the stroma or in tumor cells.